The females of Epipleoneura capilliformis (Selys, 1886) and E. albuquerquei Machado, 1964 (Odonata: Protoneurinae): description and diagnosis - Vilela, Diogo Silva; Dias-Oliveira, Tomás Matheus; Souza, Marcos Magalhães; Medina-Espinoza, Emmy Fiorella; Juen, Leandro (Zootaxa, 2024)
We describe, illustrate and diagnose two hitherto unknown females of the genus Epipleoneura Williamson, 1915: E. capilliformis (Selys, 1886) and E. albuquerquei Machado, 1964. Both females are diagnosed based on the prothoracic hind lobe morphology: in E. capilliformis, the hind lobe is trilobed, with an elevated median portion, unique within the known females of the genus. Females of E. albuquerquei have an entire, posteriorly oriented (i.e. not partitioned into additional lobes) hind lobe, similar to E. haroldoi Santos, 1964, although more concave.